Intermitochondrial cement (IMC) harbors piRNA biogenesis machinery and exonuclease domain-containing proteins EXD1 and EXD2 in mouse spermatocytes - Olotu Opeyemi; Dowling Mark; Homolka David; Wojtas Magdalena N.; Tran Panyi; Lehtiniemi Tiina; Da Ros Matteo; Pillai Ramesh S.; Kotaja Noora (WILEY, 2025)
Background
Germ granules are large cytoplasmic ribonucleoprotein complexes that emerge in the germline to participate in RNA regulation. The two most prominent germ granules are the intermitochondrial cement (IMC) in meiotic spermatocytes and the chromatoid body (CB) in haploid round spermatids, both functionally linked to the PIWI-interacting RNA (piRNA) pathway.
Aims
In this study, we clarified the IMC function by identifying proteins that form complexes with a well-known IMC protein PIWIL2/MILI in the mouse testis.
Results
The PIWIL2 interactome included several proteins with known functions in piRNA biogenesis. We further characterized the expression and localization of two of the identified proteins, Exonuclease 3 '-5 ' domain-containing proteins EXD1 and EXD2, and confirmed their localization to the IMC. We showed that EXD2 interacts with PIWIL2, and that the mutation of Exd2 exonuclease domain in mice induces misregulation of piRNA levels originating from specific pachytene piRNA clusters, but does not disrupt male fertility.
Conclusion
Altogether, this study highlights the central role of the IMC as a platform for piRNA biogenesis, and suggests that EXD1 and EXD2 function in the IMC-mediated RNA regulation in postnatal male germ cells.